Jekyll and Hyde: The monster as a metaphor - Guedes, Rodrigo Silva (Em Tese, 2008)
This essay analyses the key elements associated to the monster metaphor in Robert Louis Stevenson’s Strange Case of Dr. Jekyll and Mr. Hyde, namely, menace, impurity, freedom, pleasure, and power, based on Noël Carroll’s elaborations. The aim is to study the use of this figure represented by Hyde in the context of a strictly morally oriented Victorian society.